Game of Loyalties: Tragedy, Existentialism, and Psychoanalysis in Suikoden II - Kamarullah Kamarullah; Muhammad Arif Fadhilah; Ranti Maulya; Maulana Akbar; Shiti Maghfira (k@ta: A Biannual Publication on the Study of Language and Literature, 2026)
This study analyzes the story of the cult-classic video game Suikoden II through the lenses of Aristotelian tragedy, existentialism, and psychoanalysis. It examines how friendship, loyalty, and betrayal are represented through the relationships among Riou, Jowy, and Nanami. Using qualitative narrative analysis, supported by ludonarrative analysis, the study examines selected in-game dialogues, cutscenes, and decision-making sequences involving the three characters. The findings show that Jowy functions as an Aristotelian tragic hero whose idealistic desire to end war leads to betrayal, political power, guilt, and self-destruction. Riou is read as a silent existential agent whose identity is shaped through moral choices, imposed leadership, and the player’s decisions across different endings. Nanami is examined through psychoanalysis as an emotional anchor whose protective devotion reflects anxiety, attachment, and the desire to preserve family bonds amid war. The study argues that Suikoden II uses its character arcs and branching endings to turn loyalty, betrayal, and reconciliation into both narrative themes and player-driven moral choices.